Technical Note: Improvements in geant4 energy‐loss model and the effect on low‐energy electron transport in liquid water. Issue 7 (9th June 2015) - Kyriakou, I.; Incerti, S.; Francis, Z.
Abstract : Purpose: Thegeant 4‐DNA physics models are upgraded by a more accurate set of electron cross sections for ionization and excitation in liquid water. The impact of the new developments on low‐energy electron transport simulations by thegeant 4 Monte Carlo toolkit is examined for improving its performance in dosimetry applications at the subcellular and nanometer level. Methods: The authors provide an algorithm for an improved implementation of the Emfietzoglou model dielectric response function of liquid water used in thegeant 4‐DNA existing model. The algorithm redistributes the imaginary part of the dielectric function to ensure a physically motivated behavior at the binding energies, while retaining all the advantages of the original formulation, e.g., the analytic properties and the fulfillment of the f ‐sum‐rule. In addition, refinements in the exchange and perturbation corrections to the Born approximation used in thegeant 4‐DNA existing model are also made. Results: The new ionization and excitation cross sections are significantly different from those of thegeant 4‐DNA existing model. In particular, excitations are strongly enhanced relative to ionizations, resulting in higher W ‐values and less diffusive dose‐point‐kernels at sub‐keV electron energies. Conclusions: An improved energy‐loss model for the excitation and ionization of liquid water by low‐energy electrons has been implemented ingeant 4‐DNA. The suspiciously low W ‐values and the unphysical long tail in the dose‐point‐kernel have been corrected owing to a different partitioning of the dielectric function.